Genome-Wide Association Study Identifies New Risk Loci for Progression of Schistosomiasis Among the Chinese Population - Zhou, Miao; Xue, Chao; Wu, Zhongdao; Wu, Xiaoying; Li, Miaoxin (Frontiers in Cellular and Infection Microbiology, 2022)
Schistosoma japonicum infections, which lead to local inflammatory responses to schistosome eggs trapped in host tissues, can result in long-term, severe complications. The development of schistosomiasis may result from a complex interaction between the pathogenic, environmental, and host genetic components. Notably, the genetic factors that influence the development of schistosomiasis complications are poorly understood. Here we performed a genome-wide association study on multiple schistosomiasis-related phenotypes of 637 unrelated schistosomiasis patients in the Chinese population. Among three indicators of liver damage, we identified two novel, genome-wide significant single-nucleotide polymorphisms (SNPs) rs34486793 (P = 1.415 × 10-8) and rs2008259 (P = 6.78 × 10-8) at locus 14q32.2 as well as a gene, PMEPA1, at 20q13.31 (index rs62205791, P = 6.52 × 10-7). These were significantly associated with serum levels of hyaluronic acid (HA). In addition, RASIP1 and MAMSTR at 19q13.33 (index rs62132778, P = 1.72 × 10-7) were significantly associated with serum levels of aspartate aminotransferase (AST), and TPM1 at 15q22.2 (index rs12442303, P = 4.39 × 10-7) was significantly associated with serum levels of albumin. In schistosomiasis clinical signs, ITIH4 at 3p21.1 (index rs2239548) was associated with portal vein diameter (PVD) class, an indicator of portal hypertension, and OGDHL at 10q11.23 (index rs1258172) was related to ascites grade. We also detected an increased expression of these six genes in livers of mice with severe schistosomiasis. Summary data-based Mendelian randomization analyses indicated that ITIH4, PMEPA1 and MAMSTR were pleiotropically associated with PVD class, HA and AST, respectively.